Melatonin and andrographolide synergize to inhibit the colospheroid phenotype by targeting Wnt/beta‐catenin signaling. Issue 1 (5th June 2022) - Sokolov, Daniil; Sharda, Neha; Giri, Banabihari; Hassan, Md Sazzad; Singh, Damandeep; Tarasiewicz, Agnieszka; Lohr, Charity; von Holzen, Urs; Kristian, Tibor; Waddell, Jaylyn; Reiter, Russel J.; Ahmed, Hafiz; et al.
Abstract: β‐catenin signaling, and angiogenesis are associated with colospheroid (CSC), development. CSCs, spheroids derived from colon cancer cells, are responsible for metastasis, drug resistance, and disease recurrence. Whether dysregulating β‐catenin and inhibiting angiogenesis reduce CSC growth is unknown. In this study, the molecular mechanism of CSC growth inhibition was evaluated using a novel combination of melatonin (MLT) and andrographolide (AGP). These drugs have anticarcinogenic, antioxidant, and antimetastatic properties. CSCs were obtained from two metastatic colon cancer cell lines (HT29 and HCT‐15). The viability and stemness were monitored (FDA propidium iodide staining and immunoblot for CD44, CD133, Nanog, Sox2, and Oct4). The drug combination synergistically diminished stemness via increased reactive oxygen species (ROS) levels, reduced mitochondrial membrane potential and ATP level. MLT + AGP induced cell death by inhibiting β‐catenin expression and its downregulatory signals, Cyclin D1, c‐Myc. MLT + AGP treated cells exhibited translocation of phospho‐β‐catenin to the nucleus and dephosphorylated‐β‐catenin. Downregulation of β‐catenin activation and its transcription factors (TCF4 and LEF1) and GTP binding/G‐protein related activity were found in the dual therapy. Angiogenic inhibition is consistent with downregulation of VEGF messenger RNA transcripts (VEGF189), phosphorylated VEGF receptor protein expression, matrigel invasion, and capillary tube inhibition. In vivo, the intravenous injection of MLT + AGP slowed HT29 metastatic colon cancer. Histopathology indicated significant reduction in microvascular density and tumor index. Immunohistochemistry for caspase 7, and β‐catenin found increased apoptosis and downregulation of β‐catenin signals. The mechanism(s) of decreased colospheroids growth were the inhibition of the Wnt/β‐catenin pathway. Our results provide a rationale for using MLT in combination with AGP for the inhibition of CRCs.